Immobilization of β‐Galactosidase on Monolithic Discs for the Production of Prebiotics Galacto‐oligosaccharides. Issue 5 (1st March 2021) - Pottratz, Ines; Schmidt, Christoph; Müller, Ines; Hamel, Christof
Abstract: Four different activated methacrylatic monoliths, acting as pore‐through‐flow membrane reactors in order to reduce enzyme costs and mass‐transfer limitations, were characterized as support for immobilization of β ‐galactosidase to produce galacto‐oligosaccharides (GOS). GOS synthesis was studied in different operation modes. A higher affinity of the immobilized enzyme towards the transgalactosylation reaction could be obtained, which results in desired GOS with higher degree of polymerisation. Kinetic models were successfully parametrized forming a basis for process modeling and optimization. Abstract : Immobilization of β ‐galactosidase offers a sustainable production strategy for the synthesis of prebiotic galacto‐oligosaccharides from lactose. Methacrylate‐based convective interaction monoliths used as pore‐through‐flow enzyme reactors were investigated in different configuration to characterize kinetic parameters and enzyme activity.